Migraine and Cerebrovascular Atherosclerosis in Patients With Ischemic Stroke. Issue 7 (July 2017) - van Os, Hendrikus J.A.; Mulder, Inge A.; Broersen, Alexander; Algra, Ale; van der Schaaf, Irene C.; Kappelle, L. Jaap; Velthuis, Birgitta K.; Terwindt, Gisela M.; Schonewille, Wouter J.; Visser, Marieke C.; Ferrari, Michel D.; van Walderveen, Marianne A.A.; et al.
Abstract : Background and Purpose—: Migraine is a well-established risk factor for ischemic stroke, but migraine is also related to other vascular diseases. This study aims to investigate the association between migraine and cerebrovascular atherosclerosis in patients with acute ischemic stroke. Methods—: We retrieved data on patients with ischemic stroke from the DUST (Dutch Acute Stroke Study). Migraine history was assessed with a migraine screener and confirmed by telephone interview based on the ICHD criteria (International Classification of Headache Disorders). We assessed intra- and extracranial atherosclerotic changes and quantified intracranial internal carotid artery calcifications as measure of atherosclerotic burden on noncontrast computed tomography and computed tomographic angiography. We calculated risk ratios with adjustments for possible confounders with multivariable Poisson regression analyses. Results—: We included 656 patients, aged 18 to 99 years, of whom 53 had a history of migraine (29 with aura). Patients with migraine did not have more frequent atherosclerotic changes in intracranial (51% versus 74%; adjusted risk ratio, 0.82; 95% confidence interval, 0.64–1.05) or extracranial vessels (62% versus 79%; adjusted risk ratio, 0.93; 95% confidence interval, 0.77–1.12) than patients without migraine and had comparable internal carotid artery calcification volumes (largest versus medium and smallest volume tertile, 23% versus 35%; adjusted risk ratio, 0.93; 95% confidence interval, 0.57–1.52). Conclusions—: Migraine is not associated with excess atherosclerosis in large vessels in patients with acute ischemic stroke. Our findings suggest that the biological mechanisms by which migraine results in ischemic stroke are not related to macrovascular cerebral atherosclerosis. Abstract : Supplemental Digital Content is available in the text.